Ovarian Metastasis from Lung Cancer: A Rare Entity. (24th March 2013) - Cengiz, Huseyin; Yıldız, Şükrü; Kaya, Cihan; Şenyürek, Erdinç; Ekin, Murat; Yasar, Levent
Abstract : This paper describes a case of ovarian metastasis from lung carcinoma along with its diagnostic challenges, clinical management, and review of the literature. A 49-year-old woman was admitted to our emergency department with complaints of abdominal pain and vomiting. A laparoscopic appendectomy was performed due to acute appendicitis, and a unilateral oophorectomy (left side) via laparoscopy was performed due to the detection of an ovarian mass. Immunohistochemical staining of the ovarian mass revealed that it was reactive to cytokeratin-7 (CK-7) but negative for CK-20. The immunohistochemical and pathological features of the tumor indicated an ovarian metastasis of non-small-cell lung cancer. The patient underwent chemotherapy and was followed up by the oncology department. Her postoperative regular followup of 6 months showed that her condition was stable with no recurrence. The management of female patients with acute abdominal pain and pelvic masses should consist of a multidisciplinary approach to include the diagnosis of any distant organ metastasis.